2014
DOI: 10.1007/s00381-014-2579-0
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging findings in children with pseudotumor cerebri and comparison with healthy controls

Abstract: According to our study, posterior globe flattening, intraocular protrusion of the optic nerve, horizontal nerve sheath tortuosity, optic nerve sheath distension, and decreased pituitary gland size are reliable neuroradiological diagnostic markers for pediatric pseudotumor cerebri.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 24 publications
4
33
0
1
Order By: Relevance
“…These findings include the following: posterior globe flattening, intraocular protrusion of the optic nerve, horizontal nerve sheath tortuosity, optic nerve sheath distension, and a decrease in the size of the pituitary gland. 26 In this study, the brain MR images of pseudotumor cerebri patients were normal.…”
Section: Discussionmentioning
confidence: 77%
“…These findings include the following: posterior globe flattening, intraocular protrusion of the optic nerve, horizontal nerve sheath tortuosity, optic nerve sheath distension, and a decrease in the size of the pituitary gland. 26 In this study, the brain MR images of pseudotumor cerebri patients were normal.…”
Section: Discussionmentioning
confidence: 77%
“…Skull base crowding and prominence of arachnoid granulations were not significant. Görkem et al 26 reported similar findings in their retrospective review of 25 pediatric pseudotumor cerebri patients, reporting moderate to high sensitivities and specificities for each of these parameters. Hartmann et al 27 also found similar results and noted that compared with adolescents, prepubertal children were less likely to exhibit flattening of the globe and more likely to show perioptic arachnoid expansion, optic nerve tortuosity, empty sella, and transverse sinus stenosis.…”
Section: Diagnostic Testingmentioning
confidence: 56%
“…20 MRI findings suggestive of IH in children include: posterior globe flattening, intraocular protrusion of the optic nerve, horizontal tortuosity of the optic nerve, optic nerve sheath enlargement, and decreased size of the pituitary gland. 21,22 Lumbar puncture is indicated to measure the CSF opening pressure and to exclude meningitis. 1,23 Diagnosis of IH is made according to the modified Dandy criteria.…”
Section: Results a Total Of 53 Children With Ih Werementioning
confidence: 99%